Transposons and pathogenicity in Xanthomonas: acquisition of murein lytic transglycosylases by TnXax1 enhances Xanthomonas citri subsp. citri 306 virulence and fitness - Oliveira, Amanda C. P. [UNESP]; Ferreira, Rafael M. [UNESP]; Ferro, Maria Ines T. [UNESP]; Ferro, Jesus A. [UNESP]; Chandler, Mick; Varani, Alessandro M. [UNESP] (Peerj Inc, 2018)
Xanthomonas citri subsp. citri 306 (XccA) is the causal agent of type A citrus canker (CC), one of the most significant citriculture diseases. Murein lytic transglycosylases (LT), potentially involved in XccA pathogenicity, are enzymes responsible for peptidoglycan structure assembly, remodeling and degradation. They directly impact cell wall expansion during bacterial growth, septum division allowing cell separation, cell wall remodeling allowing flagellar assembly, bacterial conjugation, muropeptide recycling, and secretion system assembly, in particular the Type 3 Secretion System involved in bacterial virulence, which play a fundamental role in XccA pathogenicity. Information about the XccA LT arsenal is patchy: little is known about family diversity, their exact role or their connection to virulence in this bacterium. Among the LTs with possible involvement in virulence, two paralogue open reading frames (ORFs) (one on the chromosome and one in plasmid pXAC64) are passenger genes of the Tn3 family transposon TnXax1, known to play a significant role in the evolution and emergence of pathogenicity in Xanthomonadales and to carry a variety of virulence determinants. This study addresses LT diversity in the XccA genome and examines the role of plasmid and chromosomal TnXax1 LT passenger genes using site-directed deletion mutagenesis and functional characterization. We identified 13 XccA LTs: 12 belong to families 1A, 1B, 1C, 1D (two copies), 1F, 1G, 3A, 3B (two copies), 5A, 6A and one which is non-categorized. The non-categorized LT is exclusive to the Xanthomonas genus and related to the 3B family but contains an additional domain linked to carbohydrate metabolism. The categorized LTs are probably involved in cell wall remodeling to allow insertion of type 3, 4 and 6 secretion systems, flagellum assembly, division and recycling of cell wall and degradation and control of peptidoglycan production. The TnXax1 passenger LT genes (3B family) are not essential to XccA or for CC development but are implicated in peptidoglycan metabolism, directly impacting bacterial fitness and CC symptom enhancement in susceptible hosts (e.g., Citrus sinensis). This underlines the role of TnXax1 as a virulence and pathogenicity-propagating agent in XccA and suggests that LT acquisition by horizontal gene transfer mediated by TnXax1 may improve bacterial fitness, conferring adaptive advantages to the plant-pathogen interaction process.
Keywords: Lateral gene transfer; Comparative genomics; Biofilm; Xanthan gum; Tn3